Advances in Geriatric Dermatology - Chang, Anne Lynn S. (Springer International Publishing : Imprint: Springer, 2015)
This concise, easy-to-read book summarizes the current clinical evidence and basic science relating to aging and the skin, assisting the clinician in addressing skin problems in older dermatologic patients. Each chapter focuses on a particular area in which new knowledge has rapidly emerged over the past 5 years, ensuring that the book is completely up-to-date.   Recent insights into aging skin from basic and translational science are first discussed, covering the underlying genetics and the potential role of topical agents and procedures in reversing the aging process. Evidence-based prescribing in older patients is then explained, and the evidence relating to treatments for psoriasis, reviewed. Further chapters in Geriatric Dermatology address non-surgical treatment options for basal cell carcinoma, the increase in and management of sexually transmitted diseases in older dermatology patients, and cutaneous signs of elder mistreatment. Case vignettes and informative illustrations assist the reader in quickly grasping the connection between an age-related process and its clinical impact. Geriatric Dermatology is written for dermatologists, research scientists with translational interest, geriatricians, and gerontologists.